1992
DOI: 10.1002/joc.3370120506
|View full text |Cite
|
Sign up to set email alerts
|

The suburban energy balance: Methodological considerations and results for a mid‐latitude west coast city under winter and spring conditions

Abstract: Previous measurements of the urban energy balance primarily have been conducted in summertime. This paper reports the first extended set of winter-spring-time energy balance measurements for a city. The study was conducted in a suburb of Vancouver, British Columbia, from January to June 1987. It included hourly measurements of net all-wave radiation, sensible heat flux and the Bowen ratio. The anthropogenic and storage heat fluxes were modelled. A dynamic source area model was employed to ensure the modelled p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
135
4
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 180 publications
(151 citation statements)
references
References 27 publications
8
135
4
1
Order By: Relevance
“…The wintertime energy partitioning shows some major differences to that reported by Grimmond (1992) for Vancouver, British Columbia, in winter. Grimmond (1992) found that, during the daytime, 45% of the available energy was channelled into Q E , with 36% into Q H and 19% into Q S .…”
Section: Energy Partitioning In Wintercontrasting
confidence: 80%
“…The wintertime energy partitioning shows some major differences to that reported by Grimmond (1992) for Vancouver, British Columbia, in winter. Grimmond (1992) found that, during the daytime, 45% of the available energy was channelled into Q E , with 36% into Q H and 19% into Q S .…”
Section: Energy Partitioning In Wintercontrasting
confidence: 80%
“…Estimating Q F from the inventory of energy consumption is a classical approach (Grimmond, 1992;Kłysik, 1995;Ichinose et al, 1999;Sailor and Lu, 2004). This method assume that the final stage of all energy use is heat and that the delay between energy use and its restitution to heat is zero (Sailor and Lu, 2004).…”
Section: Estimates Of Q F From the Inventory Of Energy Consumptionmentioning
confidence: 99%
“…We have assumed that this value is also valid for tertiary sector buildings. According to previous studies (Grimmond, 1992;Sailor and Lu, 2004), we have neglected the input from human metabolism. The rasterization of the inventory has been carried out using a Geographical Information System (GIS).…”
Section: Estimates Of Q F From the Inventory Of Energy Consumptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cities, or parts thereof with intensive industrial or commercial activity, or where there is significant winter heating or summer air conditioning, this term may also be a significant component of the energy balance (Oke, 1987;Klysik, 1996;Ichinose et al, 1999). Q F may be estimated from energy consumption estimates and empirical traffic flow data (Oke, 1987;Grimmond, 1992;Sailor and Lu, 2004). Unfortunately, these data do not all usually match the temporal or spatial scale of the other SEB measurements and may only be compared over longer time frames.…”
Section: Introductionmentioning
confidence: 99%